Scabies Transmission and Therapeutic Outcomes in a Primary Care Setting in Bandar Lampung, Indonesia - Mira Aprilika; Triski Febrian; Tubagus Dharis Sidqi; Tyan Raga; Vio Salsabila; Wahyu Setianing Budi (Biomedical Research and Theory Letters, 2025)
Scabies is a contagious parasitic skin disease caused by Sarcoptes scabiei var. hominis, characterized by nocturnal pruritus, erythematous papules, and burrows. Transmission occurs readily in households and communities with close contact and poor hygiene. Although scabies is a common public health problem in Indonesia, clinical documentation of household transmission and integrated management strategies in primary care settings remains limited. This study aims to describe the clinical presentation, transmission pathway, and therapeutic management of scabies in a household setting, highlighting the importance of integrated treatment and hygiene measures to prevent reinfestation. A 33‑year‑old male presented to Labuhan Ratu Public Health Center, Bandar Lampung, with severe itching localized to the wrists, interdigital spaces, and genital region. Clinical examination revealed erythematous papules and burrows consistent with scabies. Diagnosis was established clinically based on cardinal signs and a history of close contact with his son, who had similar symptoms. No laboratory investigations were performed. Management included topical 5% permethrin applied according to protocol, oral cetirizine for symptomatic relief, vitamin B complex supplementation, and simultaneous treatment of all family members. Environmental interventions included washing clothes and bed linen with hot water and reinforcing personal hygiene practices. The patient demonstrated clinical improvement following therapy, with resolution of pruritus and regression of lesions. Family members treated simultaneously also showed recovery, and no reinfestation was reported during follow‑up. Vital signs and systemic examinations remained within normal limits, confirming localized disease. This case underscores the ease of household transmission of scabies and the necessity of integrated management strategies in primary care. The novelty of this report lies in emphasizing a holistic approach—combining pharmacological therapy with family‑wide treatment and hygiene reinforcement—as a practical model for scabies control in resource‑limited settings. Such documentation contributes to global understanding of scabies management and highlights the role of community health centers in addressing neglected parasitic diseases.